On Knowing and Being Known: Trust and Legitimacy in Co-Producing Desistance - Graham, Hannah (2015)
This guest blog post reflects on issues of trust and legitimacy as they relate to people with convictions and experiences of punishment, and the co-productive forums and relationships in which they take part. Attention is drawn to the relational and moral dimensions of building trust and co-producing desistance which, in return, reflect on those same dimensions of the circumstances and communities to which reintegration is sought. The co-productive ventures and forums of interest here range from mutual aid groups, peer mentoring and service user/peer advocacy forums, through to cooperatives, time banks, creative arts initiatives, and social enterprises for people with convictions, through to big picture participative social action and awareness raising campaigns. Some of these forums and ventures are positioned directly within and specifically for people in criminal justice institutions; others prefer to operate independently of institutions. Importantly, participation is chosen, not coerced